Kas yra knygos istorija? Iš anglų kalbos vertė R. Kriaučiūnienė ir A. Navickienė - Darnton, Robert (Knygotyra, 1998)
The article presents the Lithuanian translation (made by R. Kriaučiūnienė and A. Navickienė) of the publication "What is the History of Books?" by Robert Darnton. R. Darnton is a world-known book historian working at the History Department of Princeton University in the United States. For the first time author’s theoretical reflections on the question what is the history of books were publicized in the conference "Books and Society in history", which took place in Boston on 24-28 of June, 1980. In English this material is published in the proceedings of the conference - Books and Society in history Į Ed. By K. E. Carpenter. New York; London, 1983. XXIII, 254 p., and in the journal of American Academy of Arts and Sciences - Daedalus (CXl (1982), Nr. 3, p. 65-83).